The Effect of Video Conference Assisted Online Learning on Students' Mathematical Problem Solving Ability during the Covid-19 Pandemic - Marhami, Marhami; Fonna, Mutia; Mursalin, Mursalin; Nuraina, Nuraina (International Journal for Educational and Vocational Studies, 2020)
This study aims to determine whether online learning assisted with video conferencing affects students' mathematical problem solving abilities during the Covid-19 pandemic. This research is a quasi experimental research type with a quantitative approach and a nonequivalent control group design. The population in this study were all students of mathematics education at the University of Malikussaleh semester III and the sample consisted of two classes, namely the experimental class and the control class. Data collection techniques are tests of mathematical problem solving abilities that have been tested and analyzed. The data analysis technique used is using the t test with terms of normality and homogeneity. The result of the research obtained is that there is an effect of online learning assisted by video conferencing on students' mathematical problem solving abilities during the Covid-19 pandemic.